Molecular and secretory profiles of human mesenchymal stromal cells and their abilities to maintain primitive hematopoietic progenitors - Wagner, Wolfgang; Roderburg, Christoph; Wein, Frederik; Diehlmann, Anke; Frankhauser, Maria; Schubert, Ralf; Eckstein, Volker; Ho, Anthony Dick (Stem cells, 2007)
Mesenchymal stromal cells (MSC) provide a supportive cellular microenvironment and are able to maintain the self-renewal capacity of hematopoietic progenitor cells (HPC). Isolation procedures for MSC vary extensively, and this may influence their biologic properties. In this study, we have compared human MSC isolated from bone marrow (BM) using two culture conditions, from cord blood (CB), and from adipose tissue (AT). The ability to maintain long-term culture-initiating cell frequency and a primitive CD34+CD38− immunophenotype was significantly higher for MSC derived from BM and CB compared with those from AT. These results were in line with a significantly higher adhesion of HPC to MSC from BM and CB versus MSC from AT. We have compared the cytokine production of MSC by cytokine antibody arrays, enzyme-linked immunosorbent assay, and a cytometric bead array. There were reproducible differences in the chemokine secretion profiles of various MSC preparations, but there was no clear concordance with differences in their potential to maintain primitive function of HPC. Global gene expression profiles of MSC preparations were analyzed and showed that adhesion proteins including cadherin-11, N-cadherin, vascular cell adhesion molecule 1, neural cell adhesion molecule 1, and integrins were highly expressed in MSC preparations derived from BM and CB. Thus, MSC from BM and CB are superior to MSC from AT for maintenance of primitive HPC. The latter property is associated with specific molecular profiles indicating the significance of cell-cell junctions but not with secretory profiles. Disclosure of potential conflicts of interest is found at the end of this article.
First published online in Stem cells express July 5, 2007
Frontdoor: First published: 02 January 2009
Gesehen am 25.10.2021